EMPOWERING PEER EDUCATORS AND MOTIVATORS IN ELEMENTARY SCHOOL-AGE CHILDREN TO PREVENT COVID-19 - Saifah, Andi; Parmin, Parmin; Rahmawati, Sitti (LPPM Univ. Ibn Khaldun Bogor, 2023)
The use of health protocols has decreased, the achievement of Covid-19 vaccination for school-age children is 60% of the 80-90% target and all school health cadres have graduated in Tatanga District. The purpose of community service is the training of peer educators and motivators in the implementation of the School Health Business program in preventing Covid-19 transmission in Tatanga District. the method of devotion is training through lectures, simulations, and practice. The participants were 40 students and representatives from five elementary schools. Evaluation of the use of pre and post-tests and observation of educational practice. The results of the training were 36 people (90%) increased with the category of 8 people (20%) very good, 14 people (35%) good, 14 people (35%) enough, 4 people (10%) less. The results of the practice of peer educators and motivators obtained 8 people (20%) very good category, 14 people (35%) good category, 11 people (27.5%) enough category, and 7 people (17.5%) in the poor category. This service has produced 33 school health cadres who are eligible as peer educators and motivators in preventing Covid-19. The results of the evaluation after one month of training, it was found that 60% had carried out actively and independently. It is hoped that the school will further enhance the empowerment of peer educators and motivators in building a healthy and clean life in the school and family environment.